Primary Omental Lipoma in a Child: A Case Report and Literature Review - Yuan, Qiang; Duan, Xufei; Yan, Xueqiang (Frontiers in Pediatrics, 2022)
To summarize the clinical characteristics and treatment methods of primary omental lipoma in children, and to improve the diagnosis and treatment of this rare disease by pediatric surgeons. A retrospective analysis of a 6-year-old male child who was admitted to Wuhan Children’s Hospital of Tongji Medical College, Huazhong University of Science and Technology, was diagnosed with a tumor on the left upper abdomen on CT scan after an accidental fall. He had no history of abdominal pain，abdominal mass, vomiting, etc. It was found that the abdominal tumor was admitted to the hospital within 3 days, and the admission was diagnosed as intra-abdominal tumor. After admission, abdominal ultrasound and enhanced CT showed a mass in the left middle abdomen, which was 71mm×40mm×60mm. Intra-abdominal lipoma should be considered, and there was no abnormality in tumor markers. Intraoperative exploration revealed that the tumor was located in the left mid-upper abdomen, about 70mm×60mm×50mm in size, yellow, solid, soft, and isolated. Its base was derived from the greater omentum without torsion. Intraoperative diagnosis: Omental lipoma. The child received liquid food at 6 hours postoperatively, and was discharged 3 days after operation. He returned to the hospital 3 months later. Abdominal ultrasound showed no tumor recurrence.Through literature search, a total of 12 cases of primary omental lipoma in children were reported. Children are often asymptomatic and are discovered incidentally during physical examination, trauma, or examination for abdominal disease. The main symptoms of some children include abdominal pain, abdominal mass and bloating, nausea and weight loss occasionally, and a small number of children were admitted to the emergency department with torsion of the greater omentum. US and CT are recommended preoperative examinations for omental lipoma, Laparoscopic surgical resection is an effective treatment for omental lipoma. If you are admitted to the hospital due to combined torsion of the greater omentum, partial resection of the greater omentum can be performed at the same time. The postoperative recurrence rate is less than 5%, mainly due to incomplete resection. Primary omental lipoma in children is a rare benign tumor of the omentum.Laparoscopic surgery is an effective treatment.